The Students’ Strategies in Online Learning Interaction: Exploring Politeness in Google Classroom during Covid-19 Pandemic - Sembiring, Elita Modesta Br.; Sianturi, Srisofian; Simanjuntak, Faido Marudut Pardamean; Tarigan, Sri Ninta (Elsya : Journal of English Language Studies, 2021)
Teacher-student politeness has been well-explored over the years, but mostly in direct or face-to-face communication. This study aims to fill the gap of politeness between students and educators in online learning, specifically in the sessions of one of the staple and most used educational platforms during the Covid-19 pandemic, namely Google Classroom. This study applies qualitative research method by describing the phenomenon of the language. This study observed the interaction of 36 English Literature Department students during their Google Classroom sessions from April to July 2021. The researchers analysed the students’ interaction with their lecturer according to Brown and Levinson’s politeness theory. Five politeness strategies were identified, namely the positive politeness strategies (i.e., greeting, gratitude and address term), negative politeness (i.e., apology) and vernacular language. The gratitude and address term expression conveyed by “Thank you, Mam” is dominantly used by students to minimize threat when giving comments for every instruction created by lecturer. Results of this study showed that the students use politeness strategies to ensure the effectiveness of online learning, yet they also limit their text-based interaction with the short expressions of politeness such as “Hi, mam” or “Yes, mam”. This finding contributes to shedding light on the aspect of politeness in online interaction in Google Classroom and directs future studies to explore politeness in other contexts.